2019
DOI: 10.1080/14631377.2019.1607440
|View full text |Cite
|
Sign up to set email alerts
|

Inequality and historical legacies: evidence from post-communist regions

Abstract: Egalitarianism is one of the key elements of the Communist ideology, yet some of the former Communist countries are among the most unequal in the world in terms of income distribution. Russia became a country with very high levels of income inequality: according to the World Inequality Report (2016), top ten 10% of the income distribution in Russia earned 46% of the total income, which is comparable to the US level. How does the Communist legacy affect the income inequality in the long run? The goal of this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 104 publications
0
17
0
Order By: Relevance
“…What factors mitigate a self-reinforcing cycle of pandemics' impact on social and economic divisions that make the virus deadlier and more persistent? These questions face countries worldwide, but are highly pertinent to post-Soviet countries, where inequality and poverty have become -to varying degrees -enduring characteristics (Hohmann et al 2014;Libman and Obydenkova 2019). The study of the relationship between poverty and COVID-19 could be used to better understand the extent of post-Soviet social stratification resulting from development efforts and urbanization.…”
Section: Pandemics and Society: Inequalities Patriarchy Trust Netwmentioning
confidence: 99%
“…What factors mitigate a self-reinforcing cycle of pandemics' impact on social and economic divisions that make the virus deadlier and more persistent? These questions face countries worldwide, but are highly pertinent to post-Soviet countries, where inequality and poverty have become -to varying degrees -enduring characteristics (Hohmann et al 2014;Libman and Obydenkova 2019). The study of the relationship between poverty and COVID-19 could be used to better understand the extent of post-Soviet social stratification resulting from development efforts and urbanization.…”
Section: Pandemics and Society: Inequalities Patriarchy Trust Netwmentioning
confidence: 99%
“…A widespread view in the literature is that the post-communist transformation led to a significant shift in income distribution (for example see, Branko Milanović 1998;Francisco H. G. Ferreira 1999;Mitra and Yemtsiv 2006;Nauro F. Campos, Paul De Grauwe, and Yuemei Ji 2018). During transition, income equality as one of the central features of socialism has been replaced by sharp income differentiation (Irena Grosfeld and Claudia Senik 2010;Alexander Libman and Anastassia Obydenkova 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, a set of studies connects the nature, development, and effects of Eurasian regional governance to a number of profound historical issues that make the Eurasian regionalism critically different from regional governance elsewhere in the world. The literature on historical legacies in general and on post-Communist legacies in particular, has been growing in the last decades to explain democratic development, attitudes, behavioural patterns (e.g., corruption), economic development (e.g., inequality, firm innovation, development of bank sector, foreign direct investment), the mass media, political discourse and even entertainment in Central European States and in the former Soviet republics (Beissinger, 2002;Beissinger & Kotkin, 2014;Lankina et al, 2016a;Libman & Obydenkova, 2019a, 2019bObydenkova & Libman, 2015;Pop-Eleches, 2007;Pop-Eleches & Tucker, 2013). Among other issues, these studies have also indicated at the persistence and survival of profound economic and social links, especially the channels of foreign trade created during the USSR and the importance of migration and lingua franca that survives due to the mass media in Russia as well as the use of cyber-space as an entertainment.…”
Section: Differences Across Eurasian Regional Organisationsmentioning
confidence: 99%